Brava, valentine eaudiobook A novel. - Trigiani, Adriana (Valentine Trilogy, 2020)
“Delightful, energetic. . . . Trigiani is a seemingly effortless storyteller.” —  Boston Globe Award-winning playwright, television writer, and documentary filmmaker Adriana Trigiani returns with  Brava, Valentine , continuing the heartwarming and hilarious story of Valentine Roncalli, her family, her love life, and the Angelini Shoe Company. Following on the heels of the  New York Times  bestseller  Very Valentine  (hailed by People magazine as “Sex and the City meets Moonstruck”),  Brava, Valentine  is another tour-de-force from the beloved author of bestselling novels  Lucia, Lucia, The Queen of the Big Time,  and the Big Stone Gap series.